(untitled) (London Journal of Research In Science: Natural and Formal, 2025)
Theoretical work corresponding to the hope of extracting, without contradicting EMMY NOETHER theorem, a new energy present everywhere in the universe : The vacuum energy . Cyclic vibrations of a piezoelectric bridge embedded at its two ends are created thanks to the attractive, omnipresent, permanent Casimir force FCA, between two electrodes. This force FCA is controlled by an automatic Coulomb repulsive force FCO which appears , thanks to the closing of a switch n1 on a third electrode called Coulomb. Then , the resultant force on the piezoelectric bridge , FCO - FCA, straightens the bridge and gives it a kinetic energy, which will be dissipated by the force FCA. The force FCO disappears by the automatic closing of an in series with the ground switch n2, just after the opening of the switch n1 The system vibrates, creating at each vibration a peak of usable electrical power.